Hydro-ethanolic extract of Khaya grandifoliola attenuates heavy metals-induced hepato-renal injury in rats by reducing oxidative stress and metals-bioaccumulation. Issue 11 (November 2022) - Kouam, Arnaud Fondjo; Masso, Micheline; Kouoh, Ferdinand Elombo; Fifen, Rodrigue; Njingou, Ibrahim; Tchana, Angèle Nkouatchoua; Njayou, Frédéric Nico; Moundipa, Paul Fewou
Abstract: People living in developing countries are exposed to hepato-renal injuries induced by heavy metals like lead (Pb), cadmium (Cd), and mercury (Hg) since drinking water supplied is often polluted with a high concentration of those metals. Accordingly, it is necessary to search for antidotes against heavy metals poisoning. Hence, medicinal plants bearing anti-hepatotoxic properties represent a credible option; and such plant is Khaya grandifoliola . However, there is a paucity of knowledge regarding its protective effect on heavy metals-induced hepato-renal toxicity. Thus, this study was designed to assess the protective effect of the hydro-ethanolic stem bark extract of K. grandifoliola (HKG) against hepato-renal injuries induced by chronic consumption of drinking water containing high contents of Pb, Cd, and Hg; in addition to the investigation of the chemical antioxidant properties of HKG. For the antioxidant assays, HKG was tested as a potential inhibitor of lipid peroxidation, reducer of ferric and phosphomolybdenum, and scavenger of hydroxyl and 2, 2- Diphenyl-Picryl-Hydrazyl radicals. Its protective effects were evaluated by daily co-treating rats with heavy metals solution (10 mL/kg b.w) containing 0.9, 0.58, and 1.13 ppm respectively for Pb, Cd and Hg and HKG (25 or 100 mg/kg b.w) for five consecutive months; and biochemical parameters associated to liver and kidneys functions, oxidative stress and metals bioaccumulation were assessed. HKG displayed a strong antioxidant capacity (IC50/EC50 range 3.95–17.17 μg/mL) correlated to its polyphenols content and comparable to that of Ascorbic acid. Serum levels of alkaline phosphatase, alanine/aspartate aminotransferase, and creatinine; renal and hepatic content of Cd and Pb, malondialdehyde and glutathione, activities of superoxide dismutase and catalase showed the protective effect of HKG, further evidenced by histopathological analysis. Taking together, these results demonstrated that HKG alleviates heavy metals-induced hepato-renal injuries in rats by reducing oxidative stress and metals-bioaccumulation. Abstract : Heavy metals; Hepato-renal toxicity; Oxidative stress; Metals-bioaccumulation; Khaya grandifoliola .